Agronomic traits of banana genotypes in three cycles of production in Rio Branco, AC, Brazil - Oliveira, Tadário Kamel de; Lessa, Lauro Saraiva; Silva, Sebastião de Oliveira e; Oliveira, Janiffe Peres de (Pesquisa Agropecuaria Brasileira, 2008)
This work aimed to evaluate agronomic traits of banana genotypes, in three production cycles. The experimental design was a complete randomized block in split plot arrangement, with fi ve replicates, in Rio Branco, AC, Brazil. The genotypes Preciosa, Japira, Pacovan Ken, Pacovan, PA42-44, Prata-anã, ST12-31, FHIA 02, Nanicão, Grande Naine, Calipso, Ambrosia, and Bucaneiro were evaluated regarding the characters: plant height; pseudostem diameter; number of green leaves at fl owering and at harvesting; bunch development period from fl owering to harvesting; number of hands per bunch; mean fruit weight; bunch weight; and yield. The cultivars Preciosa and Pacovan Ken were the tallest ones; and the hybrids PA42-44 and FHIA 02, and the cultivars Prata-anã, Nanicão and Grande Naine were the shortest ones. The cultivars Nanicão, Ambrosia, Bucaneiro, Pacovan, Prata-anã and Grande Naine and the hybrid ST12-31 had the smallest numbers of green leaves at harvesting. The cultivar Preciosa and the hybrid FHIA 02 were the most productive. The hybrids PA42-44 and FHIA 02 show promising agronomic traits and can be incorporated to the productive system, as well as the Pacovan hybrids, already adapted and recommended for cultivation in Acre State.